L'illégalité des activités pyramidales en fonction du Code criminel - Bédard, Diane (Les Cahiers de droit, 1978)
The prohibition of pyramidal lotteries was introduced in the Criminal Code in 1935. Yet, such activities have increased since the beginning of the 1970's, especially in the province of Quebec. One should distinguish between pyramidal lotteries prohibited by the Criminal Code and pyramidal sales. Distinctions between these two concepts brought the courts to deal with nuances. Each case relates to its own facts. Considering the ingenuity of promoters of such schemes, the courts have had to unmask different forms of operations, in order to detail the constituent elements of the offence and to decide upon the validity of different defences. One might think that the question has been covered, but it will be necessary to wait and see what will be the effect of the new article 190 of the Criminal Code, which authorizes a provincial license to operate a pyramidal lottery.